1995
DOI: 10.7326/0003-4819-123-1-199507010-00003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Starting Age of Physical Activity on Bone Mass in the Dominant Arm of Tennis and Squash Players

Abstract: Bones of the playing extremity clearly benefit from active tennis and squash training, which increases their mineral mass. The benefit of playing is about two times greater if females start playing at or before menarche rather than after it. The minimal level and minimum number of years of activity necessary to produce these results, the extent to which this benefit is sustained after cessation of intensive training, and the degree to which these results can be extended to other forms of physical activity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
411
1
10

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 637 publications
(450 citation statements)
references
References 6 publications
28
411
1
10
Order By: Relevance
“…In this pQCT study of male tennis players, known to have large side-to-side differences in BMC between dominant and nondominant arms, 10,19,[22][23][24]31 we showed that the additional bone mineral in the dominant arm was mainly used for increasing the bone size, not the volumetric density of the cortical or trabecular bone. In fact, when the absolute values of the cortical and trabecular densities were compared, they seemed to be virtually constant between players and controls, and across the bone sites, except the distal radius.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In this pQCT study of male tennis players, known to have large side-to-side differences in BMC between dominant and nondominant arms, 10,19,[22][23][24]31 we showed that the additional bone mineral in the dominant arm was mainly used for increasing the bone size, not the volumetric density of the cortical or trabecular bone. In fact, when the absolute values of the cortical and trabecular densities were compared, they seemed to be virtually constant between players and controls, and across the bone sites, except the distal radius.…”
Section: Discussionmentioning
confidence: 71%
“…Previous studies of tennis players 10,18,19,23,24,31 have shown large side-to-side differences in bone mineral content (BMC) and density (BMD) between the dominant and nondominant arms, but the potential changes in bone size and geometry have remained largely unclear. In some studies, bone mineral "apparent" density (BMAD, in grams per cubic centimeter), bone geometry (bone width, cortical wall thickness [CW.Th]), and strength (cross-sectional moment of inertia [CSMI]) have been estimated from dual-energy X-ray absorptiometry (DXA) data by applying simple engineering formulas and assuming the shape of the particular bone.…”
Section: Introductionmentioning
confidence: 99%
“…This finding suggests a potential for the gymnastics loading stimulus to be overriding the natural tendency for later-maturing individuals to have less bone mass in young adulthood. However, it should also be noted that other studies suggest bone may be most responsive to mechanical loading before puberty, (42,43) which was when the current cohort was actively training.…”
Section: Discussionmentioning
confidence: 80%
“…The so far published prospective controlled exercise intervention studies, most elegant support this view (14)(15)(16)(18)(19)(20), whereas similar effects could not be found in the post-pubertal period (12). Furthermore, published data indicate that the physical activity ought to include high-impact activities (21)(22)(23)(24) and that the training should probably be initiated before or in early puberty (25), if the purpose is to reach the most beneficial anabolic skeletal effects. There is also evidence that moderate intense school-based physical education classes do increase the level of physical activity and improve the physical fitness (26).…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence that moderate intense school-based physical education classes do increase the level of physical activity and improve the physical fitness (26). Less is known if similar intervention program increase aBMD and at what age the program should be initiated (25,27). In addition, it must also be clarified if moderate intense exercise in children could influence bone width, another trait that contribute to the bone strength (28).…”
Section: Introductionmentioning
confidence: 99%